Efisiensi Pemasaran Usaha Penangkapan Gurita di Pulau Sembilan Kabupaten Sinjai - Pradilia, Andi Desiah; Gani, Imam Prawiranegara (Program Vokasi UNG, 2024)
This study aims to analyze the channels, margins, costs, and efficiency of octopus marketing in Pulau Sembilan District, Sinjai Regency. The study was conducted in 2023 using a qualitative descriptive method supported by simple quantitative analysis. Primary data were obtained through interviews with fishermen, local collectors, large collectors, and exporters, while secondary data came from literature, fisheries service reports, and scientific publications. The results showed two patterns of octopus marketing channels: (1) fishermen - large collectors - exporters, and (2) fishermen - local collectors - large collectors - exporters. The highest marketing margin was found among large collectors at IDR 5,000/kg, while the highest marketing costs were also found among large collectors due to longer distribution distances. The marketing efficiency value for all channels was <1, indicating that the octopus marketing system in Pulau Sembilan District can be considered efficient. The structure of octopus marketing institutions in the study area has been functioning well, although there are still differences in costs and margins between institutions. It is recommended that fishermen obtain broader market access and institutional support, so that the added value and welfare of key actors can be further improved.